1989
DOI: 10.3171/jns.1989.71.4.0498
|View full text |Cite
|
Sign up to set email alerts
|

Brain shift, level of consciousness, and restoration of consciousness in patients with acute intracranial hematoma

Abstract: Recently, Ropper reported that horizontal brain shift caused by acute unilateral mass lesions correlated closely with consciousness, and suggested that recovery of consciousness was unlikely to occur after surgical evacuation if the shift was insufficient to explain the observed diminution of consciousness. The authors have sought to confirm the correlation of pineal shift with level of consciousness and to assess the prognostic value of brain shift measurements in a prospective study. Forty-six patients (19 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(27 citation statements)
references
References 16 publications
1
25
0
1
Order By: Relevance
“…The relationship of poor prognosis with the presence of the midline shift and compression of the basal cistern especially in initial CCT have been reported by various researchers in the literature (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). In our study, we found that compression of basal cisterns increased overall mortality, and this finding was found to be associated with poor prognosis.…”
Section: Discussionsupporting
confidence: 72%
“…The relationship of poor prognosis with the presence of the midline shift and compression of the basal cistern especially in initial CCT have been reported by various researchers in the literature (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). In our study, we found that compression of basal cisterns increased overall mortality, and this finding was found to be associated with poor prognosis.…”
Section: Discussionsupporting
confidence: 72%
“…The clinical importance of this association is supported by the observation that four out of five fatal crashes in this study experienced midline shift, the magnitude of which is known to be the most important parameter in predicting morbidity and mortality by CT imaging. [29][30] In this study, occupants with combined basilar and cranial vault fractures had statistically significantly greater midline shift than those who did not sustain a fracture. Although fractures were only observed in 17 of the occupants, these data support reported findings that skull fractures increase the risk of TBI.…”
Section: Discussionmentioning
confidence: 59%
“…MLS continued to be an important parameter on analysis of coronal MRI images, but Ropper failed to demonstrate the relationship between vertical brain shift and clinical condition on coronal MRI [5]. Also using axial CT images, other authors confirmed midline shift at septum pellucidum as a significant predictor of outcome, but not shift of pineal body or cerebral aqueduct [6]. These seemingly contradictory results highlighted the complexity of MLS measurement, which results from the interaction between different types of intracranial tissue.…”
Section: Biomedical Engineering-applications Basis and Communicationsmentioning
confidence: 99%